Math Village: Creative Games as an Effort to Improve Children’s Counting Ability Post Covid 19 Pandemic: Kampung Matematika: Permainan Kreatif Sebagai Upaya Meningkatkan Kemampuan Hitung Anak Pasca Pandemi Covid 19 - Ariyanti, Novia; Azizah, Nuril Lutvi; Amir, Mohammad Faisal (Procedia of Social Sciences and Humanities, 2022)
This community service activity aims to overcome the problems experienced by children at the elementary school level as a result of 2 years of online learning during the pandemic. The problem are that children have difficulty in calculating fast mathematic and lack of interest in learning mathematics. The solution given are to provide guidance through basic arithmaetic operations, namely addition, subtraction, multiplication and division with the Jarimatika method and foster children’s interest in learning mathematics with creative game of snake and ladder mathematics. The subjects of this community service are grade 3, 4 and 5 elementary school student in RT.05 RW.01 Dukuh Pakis Surabaya. The method used are the preparation stage, implementation stage and evaluation stage. The children were given pre-test question to find out how fast they were able to count. After that, we game an explanation of Jarimatika and how to solve basic mathematical operation problem using Jarimatika. Furthermore, the children were invited to directly implement the Jarimatika method in the math snake and ladder game. This result of this activity are that children able to count basic operation using Jarimatika method and feel happy learning mathematics.